Faktor yang Mempengaruhi Keputusan Keuangan Masa Depan - Abdul Holik; Ahmad Kafrawi Mahmud (Politeknik Ganesha Medan, 2023)
This research tries to find factors influencing financial decision in the future. There are three variables we use here: financial decision in the future, saving decisions and trust in banking institutions. The research was conducted by involving as many 200 respondents—teachers in High School—in the Makassar City. The method to analyze is Multivariate Regression that can find impact of independent variables on dependent variable. The results of study prove that the variable of current saving decision has a significant positive impact on the variable of future financial decisions. Likewise, the variable of trust in banking institution also proves a significant positive result. From these findings, it is understood that when people have better and stronger desire to save, they tend to allocate money for the future. Also when people have trust in banking institutions, they will manage money wisely for the future. We conclude that people who like to save and believe in banking institutions will easily make financial planning due to uncertainties that they must face in the future.